2013
DOI: 10.4048/jbc.2013.16.4.410
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcomes of Different Treatment Methods for the Ipsilateral Breast of Occult Breast Cancer Patients with Axillary Lymph Node Metastasis: A Single Center Experience

Abstract: PurposeThis study compared the survival outcomes of different treatment methods for the ipsilateral breast of occult breast cancer (OBC) patients with axillary lymph node metastasis.MethodsA retrospective study was conducted in which forty OBC patients with axillary lymph node metastasis were identified out of 15,029 patients who had been diagnosed with a primary breast cancer at between 1992 and 2010. The patients were categorized into three treatment groups based on ipsilateral breast management: breast-cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
0
13
2
1
Order By: Relevance
“…Previous studies also reported similar findings. The 5-year OS of BCS, mastectomy, and no operation groups was 72.0%, 74.0%, and 87.5%, respectively, with no significant differences observed between them (p=0.49) in the study by Woo et al [ 21 ]. He et al [ 5 ] also demonstrated that there were no differences in survival rates between mastectomy, BCS, and no breast operation.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies also reported similar findings. The 5-year OS of BCS, mastectomy, and no operation groups was 72.0%, 74.0%, and 87.5%, respectively, with no significant differences observed between them (p=0.49) in the study by Woo et al [ 21 ]. He et al [ 5 ] also demonstrated that there were no differences in survival rates between mastectomy, BCS, and no breast operation.…”
Section: Discussionmentioning
confidence: 92%
“…Also the present study reports relatively low incidence rate (0.17%) when compared to generally reported rate (0.3–1.0%), since we only included OBC with pathologically negative in‐breast lesion. Woo et al reported 0.33% of incidence rate of OBC in their single center study in Korea. Second, the study group is very heterogeneous regarding the local treatments such as the extent of surgery and radiotherapy.…”
Section: Discussionmentioning
confidence: 94%
“…None of the comparative studies have shown a significant increase in rates of locoregional recurrence in patients treated with WBRT as compared to MRM. 7,14,20,21 On meta-analysis, the rates of locoregional control, distant metastasis, and mortality are similar between patients who undergo MRM and those who have ALND and WBRT. 10 The addition of WBRT when the breast is preserved is an important component of the treatment, as its omission results in a significantly higher rate of locoregional recurrence due to failure to either excise or irradiate the breast primary and perhaps a worse long-term survival.…”
Section: Discussionmentioning
confidence: 99%
“…Our subtype findings are similar to those in previously published occult breast cancer cohorts with rates of ER negativity ranging from 32% to 63% and triple-negative disease reported in 18% to 33% of cases. 10,20,22,26 …”
Section: Discussionmentioning
confidence: 99%